KONSEKUENSI ABORSI TERHADAP HAK WARIS (ANALISA PEMIKIRAN PARA FUQAHA) - Choiro Umi; Ach. Faisol; Syamsu Madyan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
The Abortion case is one concrete example, that in Life today there is no denying, so many crimes that occur in the community. Especially crimes against children and women. Abortion has always been controversial among many people including in Islamic society and caused differences of opinion among the jurists in determining the law. This study aims to find out about the laws of abortion according to the scholars and the forms of punishment that will be accepted by abortionists and especially on the consequences of inheritance. Because to prevent the rampant crime, it is necessary to add learning about this problem so that people are aware of crime. This thesis uses the Normative or Library approach method (library researc). Namely research by collecting data and information with the help of various references contained in the library space that are related to the consequences of abortion on inheritance rights (analysis of thoughts of the jurists). This research is descriptive-analytic by describing and analyzing carefully the consequences of abortion on inheritance rights (analysis of reasoning of the jurists). Kata Kunci : Aborsi, Waris, Para Fuqaha